Uji Aktivitas Antibakteri Ekstrak Etanol Daun Meniran (Phyllanthus Niruri L.) -terhadap Bakteri Staphylococcus Aureus - Nurainun Badriani; Ririn Alfa Nia (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Background: Staphylococcus aureus is a pathogenic bacterium that can cause various infections in humans. The irrational use of antibiotics has contributed to the emergence of bacterial resistance, highlighting the need for alternative antibacterial agents derived from natural products. Meniran leaves (Phyllanthus niruri L.) are known to contain bioactive compounds such as flavonoids, alkaloids, tannins, and saponins, which have potential antibacterial properties. Objective: This study aimed to evaluate the antibacterial activity of ethanol extract of meniran leaves (Phyllanthus niruri L.) against Staphylococcus aureus and to determine the most effective concentration for inhibiting bacterial growth. Methods: This experimental laboratory study employed the disc diffusion method. Ethanol extract of meniran leaves was tested at concentrations of 10%, 50%, and 70%. Chloramphenicol was used as the positive control, while DMSO served as the negative control. Data were analyzed using One-Way ANOVA. Results: Phytochemical screening revealed the presence of flavonoids, alkaloids, tannins, and saponins in the ethanol extract. The antibacterial activity test showed inhibition zone diameters of 7.45 mm, 10.35 mm, and 12.06 mm at concentrations of 10%, 50%, and 70%, respectively. Statistical analysis indicated significant differences among treatment groups (p < 0.05). Conclusion: The ethanol extract of meniran leaves (Phyllanthus niruri L.) exhibited antibacterial activity against Staphylococcus aureus. The 70% concentration demonstrated the strongest inhibitory effect on bacterial growth.